Differences in smolt status affect the resistance of Atlantic salmon (Salmo salar L.) against infectious pancreatic necrosis, while vaccine-mediated protection is unaffected - Jensen, Ingvill; Overrein, Mathias; Fredriksen, Børge Nilsen; Strandskog, Guro; Seternes, Tore (Journal of Fish Diseases, 2019)
In today's aquaculture of Atlantic salmon ( Salmo salar L.), a majority of viral disease outbreaks occur after seawater transfer. A relevant question is how the parr–smolt transformation influences the efficacy of viral vaccines and the innate resistance against viral diseases. In this study, vaccinated and unvaccinated A. salmon parr were exposed to different photoperiodic regimens (1‐, 3‐ or 6‐week continuous light—WCL). Fish groups at different stages in the smoltification process were induced, as demonstrated by differences in morphological and physiological smolt parameters. At the time of seawater transfer, the 6‐WCL group had reached a more pronounced stage in the smoltification process than the 1‐WCL group. In unvaccinated fish, the subsequent cohabitation challenge with infectious pancreatic necrosis virus (IPNV) gave a significantly higher accumulated mortality in the 6‐WCL group (87%) compared to the 1‐WCL group (39%). In the vaccinated groups, this effect was not apparent and there were no differences in accumulated mortality between the 1 WCL, 3 WCL and 6‐WCL groups. These data suggest that the resistance to IPN in A. salmon was negatively influenced by smoltification, while vaccine‐mediated protection to IPN was maintained equally well irrespective of smolt status.